Novel Therapeutic Approaches to Familial HLH (Emapalumab in FHL) - Merli, Pietro; Algeri, Mattia; Gaspari, Stefania; Locatelli, Franco (Frontiers in Immunology, 2020)
Primary Hemophagocytic lymphohistiocytosis (pHLH) is a rare, life-threatening, hyperinflammatory disorder, characterized by uncontrolled activation of the immune system. Mutations affecting several genes coding for proteins involved in the cytotoxicity machinery of both natural killer (NK) and T cells have been found to be responsible for the development of pHLH. So far, front-line treatment, established on the results of large international trials is based on the use of glucocorticoids, etoposide + cyclosporine, followed by allogeneic hematopoietic stem cell transplantation (HSCT), the sole curative treatment for the genetic forms of the disease. However, despite major efforts to improve the outcome of pHLH, many patients still experience unfavorable outcomes, as well as severe toxicities; moreover, treatment-refractory or relapsing disease is a major challenge for pediatricians/hematologists. In this article, we review the epidemiology, etiology and pathophysiology of pHLH, with a particular focus on different cytokines at the origin of the disease. The central role of interferon-γ (IFNγ) in the development and maintenance of hyperinflammation is analyzed. The value of emapalumab, a novel IFNγ-neutralizing monoclonal antibody is discussed. Available data support the use of emapalumab for treatment of pHLH patients with refractory, recurrent or progressive disease, or intolerance to conventional therapy, recently, leading to FDA approval of the drug for these indications. Additional data are needed to define the role of emapalumab in front-line treatment or in combination with other drugs.